2012
DOI: 10.1242/jeb.062711
|View full text |Cite
|
Sign up to set email alerts
|

A robotic fish caudal fin: effects of stiffness and motor program on locomotor performance

Abstract: SUMMARYWe designed a robotic fish caudal fin with six individually moveable fin rays based on the tail of the bluegill sunfish, Lepomis macrochirus. Previous fish robotic tail designs have loosely resembled the caudal fin of fishes, but have not incorporated key biomechanical components such as fin rays that can be controlled to generate complex tail conformations and motion programs similar to those seen in the locomotor repertoire of live fishes. We used this robotic caudal fin to test for the effects of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
162
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(183 citation statements)
references
References 44 publications
17
162
4
Order By: Relevance
“…Robotic systems offer the advantage of facilitating force measurement, the ability to explore a large parameter space of possible parameters, and greater control over flow visualization measurements. We believe that there will be increasing use of robotic systems in comparative biology to allow more precise understanding of the relationship between the phenotype and performance [86,87], especially where interspecific comparisons involve such distantly related species that one cannot have confidence in comparisons of biological systems or can serve as 'surrogate organisms' in cases where animal function cannot be directly observed. The design of robotic models that capture key phenotypic features of these hard-to-get species may be of use in testing the performance consequences of interspecific phenotypic differences that arise during the process of speciation.…”
Section: (C) Roboticsmentioning
confidence: 99%
“…Robotic systems offer the advantage of facilitating force measurement, the ability to explore a large parameter space of possible parameters, and greater control over flow visualization measurements. We believe that there will be increasing use of robotic systems in comparative biology to allow more precise understanding of the relationship between the phenotype and performance [86,87], especially where interspecific comparisons involve such distantly related species that one cannot have confidence in comparisons of biological systems or can serve as 'surrogate organisms' in cases where animal function cannot be directly observed. The design of robotic models that capture key phenotypic features of these hard-to-get species may be of use in testing the performance consequences of interspecific phenotypic differences that arise during the process of speciation.…”
Section: (C) Roboticsmentioning
confidence: 99%
“…The intrinsic muscle controlling the caudal fin has evolved into such a sophisticated mechanism that it can achieve complex 3D motion of the caudal fin membrane [24,[41][42]. Studies on real fish and robotic models have all demonstrated that even a symmetric caudal fin can realize asymmetric hydrodynamic function to aid the fish's manoeuvrability [26,13].…”
Section: Functional Asymmetry Of the Symmetric Fish Caudal Finmentioning
confidence: 99%
“…Earlier research focused only on the fish caudal fin itself, including the movement patterns [13], fin ray stiffness [26], tail shape [20] and even membrane thickness [43], but overlooking the critical point that the fish tail is derived from the undulatory wave of the body and is attached to the caudal peduncle, which has a maximum lateral excursion of the undulatory wave [21]. If we take the motion of the caudal peduncle and the caudal fin as a whole, we can then introduce an important motion parameter, i.e., the phase angle Φ between the fin ray and caudal peduncle motion.…”
Section: Functional Asymmetry Of the Symmetric Fish Caudal Finmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the bony rays of the fish are flexible and actually bend (Lauder, 2006) rather than simply rotate like the rigid rays used in many of the robotic ribbon fin models. Research in flexible rays in other fins, for example caudal fins (Esposito et al, 2012), will hopefully inspire similar work in future ribbon fin models to better match biological ribbon fin kinematics. This will facilitate additional progress in zeroing in on their mechanical impact on fish swimming.…”
Section: Varying Mechanical Properties Of the Ribbon Finmentioning
confidence: 94%